2004
DOI: 10.1002/ejoc.200400173
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of α,β‐Unsaturated γ‐Keto Aldehydes and New Tetronic Acid and Pyridazine Derivatives by Oxidative Transformations of Alkoxyallene‐Based Dihydrofurans

Abstract: Oxidation of 3-alkoxy-substituted dihydrofuran derivatives 6 and 11 with DDQ unexpectedly provided α,β-unsaturated γ-keto aldehydes 10 and 12. A mechanism for this new oxidative ring-cleavage is presented. Since α,β-unsaturated γ-keto aldehydes are versatile intermediates, other 3-methoxy-substituted dihydrofuran derivatives 24, 26, and 28 were prepared from lithiated methoxyallene and the corresponding aldehydes. Oxidation of dihydrofuran derivatives with DDQ and subsequent treatment with sodium chlorite furn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…[PtCl 2 A C H T U N G T R E N N U N G (CH 2 =CH 2 )] 2 and AgNO 3 afforded rather low yields or disappointing diastereomeric mixtures of bicycle 5 a. [12,13] Although AgNO 3 was less diastereoselective than [PtCl 2 A C H T U N G T R E N N U N G (CH 2 =CH 2 )] 2 (60:40 vs 100:0), it was a more efficient catalyst, affording adduct 5 a in reasonable yield. Gratifyingly, we found that Au salts were effective as 5-exo-selective hydroalkoxylation catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…[PtCl 2 A C H T U N G T R E N N U N G (CH 2 =CH 2 )] 2 and AgNO 3 afforded rather low yields or disappointing diastereomeric mixtures of bicycle 5 a. [12,13] Although AgNO 3 was less diastereoselective than [PtCl 2 A C H T U N G T R E N N U N G (CH 2 =CH 2 )] 2 (60:40 vs 100:0), it was a more efficient catalyst, affording adduct 5 a in reasonable yield. Gratifyingly, we found that Au salts were effective as 5-exo-selective hydroalkoxylation catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Solvents were dried using standard procedures. Starting materials ( p ‐methoxybenzyl)oxyallene,17 N ‐benzyl‐2,3‐isopropylidene‐ D ‐glyceraldehyde nitrone18 and syn ‐ 1b – d 1b were prepared according to literature procedures. Reagents were purchased and were used as received without further purification unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…Reactions of lithiated alkoxyallenes 2 with aldehydes 1 yield primary adducts 3 which are cyclized with potassium tert ‐butoxide to afford 3‐alkoxy‐2,5‐dihydrofurans 4 (Scheme 1) 2a. The one‐step oxidative cleavage of these substrates can be performed under various conditions: Reaction of compounds 4 with two equivalents of DDQ3 at room temperature in the presence of a proton source (water or alcohol) or by treatment with an excess of the complex formed between chromium trioxide and 3,5‐dimethylpyrazole ( 7 )4 at −20 °C leads to the α,β‐unsaturated γ‐keto aldehydes 6 . These products can also be accessed by the oxidation of the corresponding 2‐substituted 3‐alkoxyfurans 5 , but preparation of compounds with this particular substitution pattern is quite difficult 5.…”
Section: Methodsmentioning
confidence: 99%